2005
DOI: 10.1038/sj.jp.7211296
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin as a Screening Test for Late-Onset Sepsis in Preterm Very Low Birth Weight Infants

Abstract: PCT (0.5 ng/ml) is more sensitive than CRP in predicting late-onset sepsis in VLBW infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…It is noteworthy to consider that studies on EOS with a PCT cut-off <2 ng/ml were all grouped together with LOS, and the two studies focusing on LOS only [42, 47] found that the PCT at this cut-off had a better accuracy, higher specificity and similar sensitivity, if compared with studies grouping EOS and LOS. This suggests that the use of two different cut-offs could improve accuracy in these two populations: PCT cut-off could be higher for neonates with EOS than for neonates with LOS.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to consider that studies on EOS with a PCT cut-off <2 ng/ml were all grouped together with LOS, and the two studies focusing on LOS only [42, 47] found that the PCT at this cut-off had a better accuracy, higher specificity and similar sensitivity, if compared with studies grouping EOS and LOS. This suggests that the use of two different cut-offs could improve accuracy in these two populations: PCT cut-off could be higher for neonates with EOS than for neonates with LOS.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some reports claim PCT to be more sensitive than CRP [7], but others have shown that PCT lacks specificity [8] and does not have any advantage over CRP [9,10]. Serum PCT cut-off of 1.0 ng/ml and CRP cut-off of 0.8 mg/dl were comparable in identification of blood-culturepositive sepsis [11]. CRP has been shown to be useful for accurately differentiating septic and nonseptic events in neonates [12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PCT is increased (to the same levels as sepsis) after chorioamnionitis, even if the child is healthy (57). Despite these cases of false positives, PCT remains, in many cases superior to C-reactive protein (CRP) in predicting sepsis (59).…”
Section: Future Diagnostic Toolsmentioning
confidence: 99%